2004
DOI: 10.1046/j.1468-1331.2003.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vascular disease on late onset Parkinson's disease

Abstract: The clinical severity of late onset Parkinson's disease (PD) varies from patient to patient and it is further complicated by the increasing prevalence of accompanying disorders in the elderly. We set out to study the impact of ischemic heart disease, minor stroke, hypertension and diabetes mellitus in a group of late onset PD patients (age >or=70 years). Consecutive late onset PD patients seen in the Department of Neurology, Medical School of Patras, Greece were included in this study. We used very strict crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Although similar post-mortem findings have been reported in age-matched controls, it is suspected that these vascular changes may have a significant impact on the presentation of nonmotor symptoms, such as CI, in persons with PD [10] [11]. In late onset PD, clinically symptomatic vascular pathology in the form of minor stroke (in addition to diabetes and ischemic heart disease) resulted in higher Hoehn & Yahr scores, suggesting that cerebrovascular changes had an effect on PD progression [13]. Finally, several studies have shown that cerebrovascular dysfunction presents in the form of widespread cerebral hypoperfusion in persons with PD [14]- [16].…”
Section: Introductionsupporting
confidence: 52%
“…Although similar post-mortem findings have been reported in age-matched controls, it is suspected that these vascular changes may have a significant impact on the presentation of nonmotor symptoms, such as CI, in persons with PD [10] [11]. In late onset PD, clinically symptomatic vascular pathology in the form of minor stroke (in addition to diabetes and ischemic heart disease) resulted in higher Hoehn & Yahr scores, suggesting that cerebrovascular changes had an effect on PD progression [13]. Finally, several studies have shown that cerebrovascular dysfunction presents in the form of widespread cerebral hypoperfusion in persons with PD [14]- [16].…”
Section: Introductionsupporting
confidence: 52%
“…Clinicopathological studies suggest that cerebral microvascular diseases (eg, white-matter lesions and cerebral amyloid angiopathy) are likely to contribute to the clinical expression and deterioration of idiopathic PD symptomatology. 23,24 Therefore, hypertension and elevated BP can be linked to PD by affecting the nondopaminergic subcortical structures. Second, chronic high BP causes hypertensive vasculopathy in the basal ganglia, thalamus, and brain stem, 25 which may affect dopaminergic cells in the pars compacta and break the connections between neurons in the substantia nigra and the putamen portion of the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of vascular encephalopathy in PD patients ranges from 6% to 44% according to different series (Chang et al, 1992;Piccini et al, 1995;Jellinger et al, 2003), and similar prevalence rates have been found in other forms of parkinsonism, such as progressive supranuclear palsy (35%) (Dubinsky et al, 1987). In addition, the presence of vascular encephalopathy, or even the existence of vascular risk factors, may aggravate the symptomatic picture in a patient with known PD (Papapetropoulos et al, 2004). The most relevant clinical characteristics of VP include: gait disorder, predominance in lower half of the body, postural instability, stiffness, pyramidal signs, and poor or no response to Ldopa (Tolosa et al, 1984;Trenkwalder et al, 1995), all of them occurring in a patient with evidence of cerebrovascular damage with no signs of other degenerative diseases, intake of antidopaminergic drugs, or hydrocephalus that could induce parkinsonism.…”
Section: Vascular Pseudoparkinsonism (Vp)mentioning
confidence: 85%